(untitled) (Economic studies journal, 2021)
Abstract The study aimed to know the impact of the application of Law No. 1 of 2013 relating to the prevention of dealing in interest, which led to the transformation of the entire Libyan banking sector to Islamic banking, by evaluating the financial performance before and after the transition to Islamic banking through the use the PATROL Model approved by the Italian banking evaluation system. The PATROL Model is based on five indicators: capital adequacy, credit quality, Organization, profitability, and liquidity, by applying to the Jumhouria Bank, through analyzing the financial data of the last financial year before the transition (the year 2012) and the data of first year financial after the complete transformation of Islamic banking (the yere 2015). The study reached several results, the most important of which are: The financial performance of the bank was negatively affected after the bank’s conversion to Islamic banking, as the capital adequacy, profitability, and Organization indicators decreased, in addition to the decline in the bank’s rating from the first (excellent) rank before the application of the Law in the year 2012 AD to the rank The third (good) after applying the Law according to the results of analyzing the bank’s data for the 2015 AD.